OECD Imports : Diversification and Quality Search - Cadot, Olivier; Carrere, Celine; Kukenova, Madina; Strauss-Kahn, Vanessa (2012)
This paper explores the evolution of OECD imports over time and as a function of income levels, measuring the concentration of those imports across origin countries at the product level. The authors find evidence of diversification followed, in the last years of the sample period (post-2000), by a slight re-concentration. This re-concentration is entirely explained by the growing importance of Chinese products in OECD imports. They also find evidence of relatively more volatile concentration levels for differentiated goods, consistent with a simple model of adverse selection and screening of suppliers by OECD buyers. Finally, they find that "accession" to OECD markets occurs directly (rather than after acquiring prior export experience on other markets) for more than half of the (extra-OECD) exporter/product pairs, but that one to eight years of experience enhances subsequent survival on OECD markets. Exports that reach OECD markets after more than eight years of experience elsewhere tend to survive less.